KUALITAS KAYU LAMINASI DENGAN PEREKAT TANIN DARI EKSTRAK KULIT KAYU MAHONI - Adi Santoso; Efrida Basri; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 2020)
Chemical components of polyphenols extraction products from mahogany wood (Swietenia macrophylla) andcopolymerized with resorcinol and formaldehyde in alkaline condition, resulting in a resin that can be used as an adhesive.This paper presents the use of tannin from mahogany bark extract copolymer as laminated wood adhesives. Researchmethods include adhesive formulations, testing of the physical-chemical properties of adhesives, manufacture and qualitytesting of the laminated products, and data analysis. The treatments imposed in this study were adhesive formulations,wood species used as raw materials, and types of products made. The results show that the copolymerized tannin extractfrom mahogany bark could be used as an adhesive in making laminated wood beams (glulam) and laminated boardsof the three wood species i.e. tusam (Pinus merkusii), jabon (Anthocephalus cadamba), and sengon (Falcatariamoluccana). The bonding quality and mechanical properties of both types of laminated products were comparable withthose of similar products glued with the imported exterior adhesive with low formaldehyde emission, and classified as F** or F *** with the adhesive ratio of T:R:F = (1:0.025:0.1)%, and T:K:F = (1:0.03:0.1)%.